#TITLE_ALTERNATIVE# - ARDHITASARI LUMBAN GAOL (NIM 15107066); Pembimbing: Dr. Ir. Dina Anggreni, M.T., dan Dr. Irw, YUSTISI
Sumatran is surrounded by Indo-Australian plate and Eurasian. Both plates are colliding along off the coast of Sumatra where the Indo-Australian plate is moving under the Eurasian. These collisions produce energy and stored in layers of earth until the limit of elasticity. Strain that has crossed the limit will be released as an earthquake. Deformation monitoring of Sumatran carried out to study the characteristics of displacement and tectonic activity that happened. Vector data of displacement is only available at some point of observation. Moving average interpolation is used to estimate the magnitude of vector of displacement that happened across the Sumatran. Vector of displacement at the interpolation point is then used to calculate the amount of strain that occurs. Vector model of displacement in Sumatran base on interpolation indicates interseismic and postseismic activity. Interseismic characterized by the displacement to the northeast and postseismic to the southwest.